The potential global gains in health and revenue from increased taxation of tobacco, alcohol and sugar-sweetened beverages: a modelling analysis. Issue 3 (29th March 2020) - Summan, Amit; Stacey, Nicholas; Birckmayer, Johanna; Blecher, Evan; Chaloupa, Frank J; Laxminarayan, Ramanan
Abstract : Introduction: Globally, a growing burden of morbidity and mortality is attributable to lifestyle behaviours, and in particular to the consumption of tobacco, alcohol and sugar-sweetened beverages (SSB). In low-income and middle-income countries, this increased disease burden falls on already encumbered and resource-constrained healthcare systems. Fiscal policies, specifically taxation, can lower consumption of tobacco, alcohol and SSB while raising government revenues. Methods: We simulated the health and economic effects of taxing cigarettes, alcohol and SSB over 50 years for 30–79 years old populations using separate mathematical models for each commodity that incorporated country-level epidemiological, demographic and consumption data. Based on data availability, national-level health effects of higher tobacco, alcohol and SSB taxes were simulated in 141, 166 and 176 countries, respectively, which represented 92%, 97% and 95% of the global population, respectively. Economic effects for tobacco, alcohol and SSB were estimated for countries representing 91%, 43% and 83% of the global population, respectively. These estimates were extrapolated to the global level by matching countries according to income level. Results: Over 50 years, taxes that raise the retail price of tobacco, alcoholic beverages and SSB by 20% could result in a global gain of 160.7 million (95% uncertainty interval (UI): 96.3 to 225.2 million), 227.4 million (UI: 161.2 to 293.6 million) and 24.3 million (UI: 15.7 to 35.4 million) additional life years, respectively. Conclusion: Excise tax increases on tobacco, alcohol and SSB can produce substantial health gains by reducing premature mortality while raising government revenues, which could be used to increase public health funding.